Salt Consumption, Knowledge, Attitude and Practices: The Intervention to Reduce Salt Intake on University Students - Gökmen, Elif; Aktaş, Nazan (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2024)
High salt intake, one of the modifiable unhealthy eating habits, causes important health problems such as hypertension, cardiovascular diseases, cancer, osteoporosis, and kidney diseases. The objective of this study is to examine the impact of educational intervention on university students' salt-related knowledge, attitudes, and practices (KAP). This intervention study was carried out at Selcuk University in Türkiye. A total of 30 students were included in this intervention study carried out using the pretest-posttest control group experimental model. The educational intervention consisting of 14 sessions was completed in six weeks. The salt intake of male students in the experimental group in the pre-test and the control group in the pre-test and post-test was found to be significantly higher than that of female students (p 0.05). The mean daily salt intake in the experimental group compared to the pre-test decreased by about 1,834 mg after intervention (p 0.05). There was a significant difference (p 0.05) between the knowledge and attitude pre-test and post-test scores of the experimental group students. The intervention study positively affected the students' salt-related KAP. In order for this effect to continue for a lifetime, educational interventions should be reproducible and sustainable.